Design concepts in nutritional epidemiology - Margetts, Barrie M.; Nelson, Michael, Dr. (Oxford : Oxford University Press, 1997)
The second edition of Design Concepts in Nutritional Epidemiology presents the latest methods for examining the complex relationship between diet and disease.
Previous ed.: 1991.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nutritionally induced diseases -- Epidemiology